Diluted Blood: Identity and the Other in Three Novels by Doeschka Meijsing - Lammer, Christina (Werkwinkel, 2016)
Two hypotheses on identity lay at the core of this paper. (1) Doeschka Meijsing presents identity as unstable and as a construct of one’s own in three novels. (2) Meijsing uses memory discourses and cultural phenomena to display how characters struggle when (re-)constructing their identities. Pip (Over de liefde, 2008), has to deal with the secret affair of her female lover who has got pregnant. She refuses to be the ‘left one’ everyone feels pity for. As a result, she has to create a new identity that doesn’t fit the expectations of others. In 100% Chemie (2002), an unnamed daughter of a German migrant and Dutch father grew up in the Netherlands. As she doesn’t identify with any nationality she seeks to stabilize her fragmented identity. Investigating the history of her German family she tries to create her own identity. Robert Martin, main character of De tweede man (2000), struggles with the legacy of his brother Alexander who has passed away. Robert has not only inherited his brother’s fortune but also his friends. They want Robert to replace Alexander. Robert has to create a new identity which fits their lifestyle. Meijsing’s characters feel as if they have ‘lost’ their identities, as far as they ‘owned’ ones. As a result, their stories stress views on identity: do they have fixed identities, which can be destroyed? Is identity a construction and if so, how can it be created? I discuss how cultural memory, especially counter-memory which questions memory discourses, impacts the construction of identity. Furthermore, I show how intersections of identity categories trouble Meijsing’s characters.